BUSINESS STRATEGY OF PT MONANG SIANIPAR ABADI (MSA) CARGO SOEKARNO HATTA CENGKARENG IN 2015 - Agus Setiawan; Jenenissa Jenenissa (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2016)
PT Monang Sianipar Abadi (MSA) Cargo is freight forwarding company that serve in shipping goods domestically and internationally, customs clearance and imported warehouse sales or warehousing.  MSA Cargo has some branches that focus more on import division to increase imported warehouse space.  The objective of this study is to find out the exact business strategy of this company by using SWOT analysis method.  The result of the study shows that the company strategy is horizontal strategy.  This strategy is gained from 2 SWOT matrix methods, which are IE matrix and SPACE matrix whose data are produced from the result of IE evaluation Matrix with the internal factor of (3.01) and the external factor of (2.98) for IE matrix data and for SPACE matrix, the data are gained from IE evaluation matrix balanced total with the horizontal X axis of (0.63) and vertical Y axis of (0.84).  Therefore, by using the integration of horizontal strategy, the company will have a big control of the competitor companies.